(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Objective: To evaluate the effectiveness of campus tobacco control activities based on advocacy-motivation theory and explore effective strategies for university tobacco control education. Methods: A cross-sectional intercept survey was conducted during a World No Tobacco Day campaign at a university in Beijing. Data were analyzed using SPSS 21.0 software. Results: At the cognitive level, participants’ awareness of smoking-related risks (stroke, heart disease, impotence, and blindness) significantly increased after the activity (P<0.05). At the attitude level, overall support for tobacco control policies was high. At the behavioral level, participants showed strong long-term behavioral intentions and smoking refusal intentions. Gender was not a significant factor in policy support or behavioral intentions. Conclusion: Campus tobacco control activities guided by advocacy-motivation theory can effectively increase college students’ awareness of tobacco hazards. Youth tobacco control requires joint participation from parents, schools, and society, along with strengthened control policies for both conventional and electronic cigarettes.